Synthesis and characteristics of Fe/Ni/Cr oxide nanoparticles/PLA hybrid composite coatings on Mg–Zn–Ca alloy - Prakash Kumar; Aditya Kudva S; AnilKumar T; Ramesh S; M.R. Ramesh; Ashwini Prabhu; Gajanan Anne (Journal of Materials Research and Technology)
Biodegradable materials research is dominated by magnesium and alloys thereof due to their excellent compatibility with biological barriers and biomechanical strength. Despite this, the rapid degradation of these materials in the physiological environment is the primary obstacle hindering their utilization in biomedical applications. This issue must be resolved before considering their use in clinical applications. To improve resistance towards corrosion and enhance biological efficacy and compatibility, the surfaces were coated with polylactic acid (PLA) using dip-coating.In this study, iron (Fe), nickel (Ni), and chromium (Cr) oxide nanoparticles from the Coleus amboinicus extract are synthesized and mixed with PLA to develop hybrid composite coatings, which are then applied onto the Mg–4Zn–1Ca alloy. Coleus amboinicus is known for its various medicinal properties, including immunoregulatory effects, antimicrobial activity, anti-inflammatory properties, and potential use in treating sepsis and other ailments. The extracted FeNiCr was used the develop composite coatings on Mg–4Zn–1Ca alloy. The coating improves biocompatibility, antibacterial properties, and overall performance of biomedical implants. These composite coatings were evaluated for their morphological and optical characteristics using a scanning electron microscope (SEM), 3-D non-contact profilometer, Fourier transform infrared spectroscopy (FTIR), and X-ray diffraction (XRD). The corrosion characteristics of developed samples were measured by electrochemical corrosion in standard simulation body fluid (SBF) at 37 °C. Furthermore, cytocompatibility of the PLA hybrid composites on osteoblast cells and apoptosis detection using acridine orange-ethidium bromide. Our developed coating showed ratings of 5B and 4B were obtained for FeNiCr/PLA NC- ball burnished (BB) Mg and FeNiCr/PLA nano composite (NC)–Mg samples, respectively, demonstrating the exceptional coating strength and the substrate. The corrosion rate of the FeNiCr/PLA NC-BB-Mg sample (0.02890 mm/y) is two-fold times increased against comparison with the H Mg sample (0.00012 mm/y). Cytocompatibility indicates their cytocompatibility for bone implant applications.